Engineering electrical properties of graphene: chemical approaches. (1st December 2015) - Kim, Yong-Jin; Kim, Yuna; Novoselov, Konstantin; Hong, Byung Hee
Abstract: To ensure the high performance of graphene-based devices, it is necessary to engineer the electrical properties of graphene with enhanced conductivity, controlled work function, opened or closed bandgaps, etc. This can be performed by various non-covalent chemical approaches, including molecular adsorption, substrate-induced doping, polymerization on graphene, deposition of metallic thin films or nanoparticles, etc. In addition, covalent approaches such as the substitution of carbon atoms with boron or nitrogen and the functionalization with hydrogen or fluorine are useful to tune the bandgaps more efficiently, with better uniformity and stability. In this review, representative examples of chemically engineered graphene and its device applications will be reviewed, and remaining challenges will be discussed.